Peran Bermain Musik Untuk Menstimulasi Area Bermain Temporal - Yati, Harlinda (Yayasan Darussalam Bengkulu, 2025)
This study aims to determine the role of playing music in stimulating the temporal play area of early childhood. Music is very important and needs to be developed for children of this age to help their development. However, many parents do not understand the importance of music for children's intelligence. Music is a medium for expressing one's mood. The importance of music for early childhood includes increasing creativity and imagination, can improve and teach other intelligences, and can stimulate children's memory. This study uses the SLR (systematic literature review) method which is applied to identify, observe, and assess relevant research to answer the researcher's questions. Researchers using the SLR method have stages: compiling questions with the required topics, the process of searching for sources used such as sources from Google Scholar, selecting various sources obtained according to the data used, and reviewing and selecting results obtained from the previous process such as titles and abstracts reviewed to determine whether the research is relevant. And from several research results show the positive impact of playing music to stimulate children's temporal play area